Francis Bacon, José de Acosta, and Traditions of Natural Histories of Winds. Issue 4 (1st October 2020) - Martin, Craig
ABSTRACT: It is well attested that Francis Bacon considered his History of Winds to be an exemplar, but what lessons should be taken from its example have been subject to debate. Instead of looking at this work as a mere model for the fusion of natural history and natural philosophy, it is also possible to see Bacon as trying to provide tentative solutions to outstanding questions regarding the wind, a topic that was deeply scrutinized during the early modern period. An examination of Bacon's provisional concluding rules reveals deep correspondences with earlier works, such as José de Acosta's Natural and Moral History of the Indies, that revised classical understandings of the wind based on experience, experiments, and accounts of travels beyond Europe. Understanding the History of Winds as a genuine attempt to solve outstanding questions about the wind uncovers its debt to earlier traditions, including those related to Renaissance natural history, and shows it's influence in relation to specific theories of the wind beyond its call for methodological reform.